Triiodobenzoic acid affects the regenerative competence in root explants of Adenocalymma nodosum (Bignoniaceae) - Paiva Neto, Vespasiano; Oliveira, Janaina Fernanda de; Sanches, Luciana Guimarães; Zuffo Borges, Monica Cristina Rezende; Cruz, Ana Claudia Ferreira da; Otoni, Wagner Campos (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
Adenocalymma nodosum, a native plant species from Brazilian Savanna, has a very interesting propagation mechanism by root segments, mainly, in areas with plants mechanical control or soil prepare by farming equipment such as plough that results in the cited root segments, enabling high regenerative capacity to generate adventitious shoots. This regenerative competence of root segments, without exogenous plant growth regulators, was previously showed to occur on in vitro conditions. Aiming to study the effect of the auxin transport inhibition on the regenerative capacity of the root segments of this species, root explants were placed in different orientations (horizontal, upright and inverted upright) on Murashige and Skoog medium added or not with triiodobenzoic acid (TIBA). It was possible to verify that root explants have a polar response with shoot buds being directly differentiated from pericycle cells only at root proximal ends. Use of TIBA, an auxin transport inhibitor, inhibited organogenesis and induced callogenesis, showing that auxin transport is essential to the favorable hormonal balance to bud differentiation at the explant proximal end.